Penetrating Fishhook Ocular Injury: Challenging management in low- resource country: Poster Presentation - Case Report - General practitioner - Nafisa Naaz Nisha; Andronico Ly (Majalah Oftalmologi Indonesia, 2023)
Introduction : Fishing is a common income source in rural areas, but fishhook eye injuries are rare. This report describes a case of a rare penetrating fishhook ocular injury, which resulted in endophthalmitis and eye evisceration, and highlights the challenges caused by delayed referral and limited options for intravitreal antibiotics due to inadequate consumable availability. Case Illustration : A 13-year-old boy from Vanuatu had a fishhook in his right eye and was referred to an Ophthalmologist one day later due to unavailability of flights. Upon arrival, endophthalmitis signs were noted, with the left eye having a visual acuity of 6/7.5 and the right eye showing only hand movement. The right eye showed corneal edema and a blood stain around the fishhook, fresh keratic precipitates, discharge and conjunctival edema. The fishhook was removed, and the cornea repaired under local anesthesia. On Day 1 post-operation, Intravitreal vancomycin and moxifloxacin were administered after procuring privately from pharmacies outside the hospital. However, the patient's condition worsened, requiring evisceration of the right eye. Discussion : Prompt management of penetrating eye injuries is crucial, with patients requiring broad spectrum antibiotics, tetanus shots, and an eye shield during referral. However, challenges such as lack of an eye shield and transportation delays worsened the patient's condition before arrival. This case also highlights the challenges faced in treating the patient effectively by the ophthalmologist due to limited options intravitreal antibiotics. Conclusion Timely management and urgent referral are crucial in low-resource areas to prevent complications. Essential consumables are necessary for effective treatment by an ophthalmologist.